Motivation For Learning In Virtual Environments, Online Self-Regulated Learning, And Writing Performance Of OMSC Students - Veronica F. Magay, MAT, Ma.; D. Gorospe, EdD, Joan (International Journal of Educational Research & Social Sciences, 2022)
This study aimed to assess students’ independent study strategies by looking through their motivation for learning in virtual environments, online self-regulated learning, and writing performance. A descriptive-correlation and predictive method of research were used in this study. Respondents of the study were 150 first year college students who were enrolled in the online classes of the course, Purposive Communication and were identified using proportional random sampling. Several instruments were used by the researcher including the survey questionnaires about motivation and online self-regulated learning as well as the students’ online writing outputs in Purposive Communication. Students’ writing performance was measured using an adapted rubric. Results of the study revealed that college students have high level of motivation for learning in virtual environment in terms of autonomous and controlled while low in terms of demotivation. Overall, the college students have high level of online self-regulated learning. Moreover, college students have high level of performance in writing as to the content, organization, vocabulary and style while moderate in terms of grammar and mechanics. Findings also revealed that there is significant relationship between motivation for learning in virtual environments and online self-regulated learning, between motivation for learning in virtual environments and writing performance, and between online self-regulated learning and writing performance. Moreover, results yield thatcontrolled motivation predicts online self-regulated learning, autonomous motivation predicts wiring performance as well as persistence. This study concluded that the higher the motivation and online self-regulated learning, the higher the writing performance of the students.